Prevalence of asymptomatic malaria parasitaemia following mass testing and treatment in Pakro sub-district of Ghana - Ignatius Cheng Ndong; Daniel Okyere; Juliana Yartey Enos; Benedicta A. Mensah; Alexander Nyarko; Benjamin Abuaku; Alfred Amambua-Ngwa; Corinne Simone C. Merle; Kwadwo Ansah Koram; Collins Stephen Ahorlu (BMC, 2019)
Abstract Background Global efforts to scale-up malaria control interventions are gaining steam. These include the use of Long-Lasting Insecticide Nets, Indoor Residual Spraying, Intermittent Preventive Treatment and Test, Treat and Track. Despite these, the drive for malaria elimination is far from being realistic in endemic communities in Africa. This is partly due to the fact that asymptomatic parasite carriage, not specifically targeted by most interventions, remains the bedrock that fuels transmission. This has led to mass testing, treatment and tracking (MTTT) as an alternative strategy to target asymptomatic individuals. We report the impact of MTTT on the prevalence of asymptomatic malaria parasitaemia over a one-year period in Ghana, hypothesizing that implementing MTTT could reduce the rate of asymptomatic parasitaemia. Methods A population of about 5000 individuals in seven communities in the Pakro sub-district of Ghana participated in this study. A register was developed for each community following a census. MTTT engaged trained community-based health volunteers who conducted house-to-house testing using RDTs every 4 months and treated positive cases with Artemisinin-based Combination Therapy. Between interventions, community-based management of malaria was implemented for symptomatic cases. Results MTTT Coverage was 98.8% in July 2017 and 79.3% in July 2018. Of those tested, asymptomatic infection with malaria parasites reduced from 36.3% (1795/4941) in July 2017 to 32.9% (1303/3966) in July 2018 (p = 0.001). Prevalence of asymptomatic parasitaemia among children under 15 years declined from 52.6% (1043/1984) in July 2017 to 47.5% (820/1728) in July 2018 (p = 0.002). Implementing MTTT significantly reduced asymptomatic parasitaemia by 24% from July 2017 to July 2018 after adjusting for age, ITN use and axillary temperature (OR = 0.76, CI = 0.67, 0.85 p ≤ 0.001). Conclusion This study has demonstrated that implementing MTTT is feasible and could reduce the prevalence of asymptomatic malaria parasitaemia in children under 15 years of age. Furthermore, the use of community-based health volunteers could ensure high coverage at lower cost of implementation. Trial registration NCT04167566, Date 14/11/2019. Retrospective registration.